An Emergency Call: The Mental Health of Teenagers in Two Novels and a Video Game - Saravia Vargas, Juan Carlos (2020)
This article compares and contrasts two novels and video games where the participation of teenage characters who battle against mental illnesses becomes fundamental to support the narrative of the text. The objective is to analyze the representation of clinical depression in Vizzini’s It’s Kind of a Funny Story, the depiction of obsessive-compulsive disorder (OCD) in Ness’s The Rest of Us Just Live Here, and the portrayal of schizophrenia in the video game Hellblade: Senua’s Sacrifice (by Ninja Theory) to assess how the texts represent mental illnesses and their social implications. The analysis shows that the three texts succeeded at creating a positive portrayal of the mental illnesses by removing generalized stereotypes about the conditions and by actively engaging readers, which fosters empathy.